PENGEMBANGAN CBT INTERAKTIF SEBAGAI INSTRUMEN PENILAIAN PEMBELAJARAN FISIKA SMA - Indah Febriani; Fauzi Bakri; A. Handjoko Permana (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
This research intent to develop computer-based estimation software or Computer Base Test (CBT) interactive as instrumental as Physics learning estimation SMA. This CBT was developed utilizes application Wondershare Quiz Creator. Observational model that is utilized in this research is model observational developmental Walter Dick, Lou Carey and James O.Carey already being modified by Atwi Suparman which is Instruksional's Development Model (MPI). Estimation instrument utilize Likert's scale. This CBT's product have passed through quiz validates by media expert and an estimation expert with percentage 91,50% and 93,75%. Averagely percentage usufructs to test validates by media expert and estimation expert be 92,63% by pretty good estimation categories. Circumscribed test-driving or smallscale by class student X MIA SMAN 22 Jakarta gets to increase estimations very good with percentage 82,14%. After tests to validate by media expert, estimation expert, and circumscribed quiz, done by revision on CBT's application. Hereafter, done by test-driving by educator which is physics teacher of SMAN 31 Jakarta and scale test-driving outgrows by class student X MIA SMAN 31 Jakarta. Percentage usufructs test-driving by educator be 98,22%, meanwhile scale test-driving result outgrows by student be 74,86%. Base quiz result validates by media expert, estimation expert, smallscale test-driving by student, test-driving result by educator, and scale test-driving result outgrows by student, can be concluded that CBT already being developed by researcher has very good criterion and reasonable be utilized as instrument of physics learning estimation SMA. Key word : CBT, Estimation instrument, Physics learning of SMA, Instruksional's Developmental Model (MPI).